PENERAPAN AL-QARDL PADA BANK KELILING (STUDI KASUS DI GRUGEK DESA SEJATI KECAMATAN CAMPLONG KABUPATEN SAMPANG) - Sakinah Sakinah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
owe (al-qardl) is one of the transactions that is allowable in Islam. To lend, from the perspective of fiqh muamalah it is known as al-Qardl, is the process of hand over of wealth or al-mitsliyat to other people that the payment must be collected. In other word, it is a transaction that aimed to give al-mitsliyat over other people to be recollected with the similar al-mitsliyat. This kind of transection had been done in the era of prophet. As it becomes a phenomenon at Grugek, one of the sub-villages of Sejati village, Camplong district in Sampang regency. In Grugek, people owe money from a mobile-bank mostly for a consumptive objective and only a few of them use the money for something productive. Based on this phenomenon, the research is focused on the following problems: (a) how is the implementation of al-qardl transection promoted by mobile bank in Grugek sub-village, Sejati Village, Camplong district, Sampang Regency? (b) Why do people of Grugek sub-village, Sejati Village, Camplong district, Sampang regency tends to owe money from the mobile-bank than from official bank? This is a qualitative field research in form of case study that employs the result of interview and observation as primary data. The instruments that have been used to collect and check the data validity are intent observation, description, triangulation, and case analysis.  The research result designates that: (1) the implementation of al-qardl is completed in easy ways; showing ID, no prerequisite and regulation as must be fulfilled in fiqh muamalah about the execution of interest in its implementation; (2) the people of Grugek owe money from mobile bank with several reasons: firstly, the process of credit is simpler than official bank does, easiness, no survey, only ID identification, people are allow to owe many times; secondly,  people still do not know syariah finance institution that offers the product of al-qardl al-hasan.